An ergonomics and online marketing applications in leather products industry - E Nurmianto; B Amaliah; A Anzip (Institut Teknologi Sepuluh Nopember, 2018)
Leather Handicraft Products has been fostered through IBPE (Ipteks Bagi Produk Ekspor) Program In Sidoarjo District, East Java Province to improve the management of SME (Small and Medium Enterprises) development covering management, marketing, human resources and facilities. SMEs that become partners are CMP and DJA. The products produced by both SMEs are products with high quality leather raw materials. Both SMEs wish to expand their business to foreign level but are constrained by quality, unqualified labor, and quality. From the menu then as a form of community service, researchers conduct training and mentoring which includes: Training 1: Online Marketing Training, Training 2: Occupational Health and Safety, Training 3: Practical English Training, Training 4: Website Creation Mentoring,. Finally expected after the above training, both SMEs can develop abilities to the level overseas and the results of this service can be a reference for other researchers to improve the welfare of SMEs in Indonesia. Ergonomics is applied in accordance with solution in all sectors.